Media discourse of national identity: Russia and Germany: Медиадискурс национальной идентичности: Россия и Германия - Kaminskaya, Tatyana (Przegląd Wschodnioeuropejski, 2021)
The media discourse of both Russia and European countries today seems to be a representative and relevant object for the study of national identity. The discourse of national identity in the media is presented as media texts directly related to the topic, and included in it through the comments of the recipients. The leading sub-discourses or thematic dominants in this case are major sports competitions, international competitions and commemorative practices of the past. The vast majority of assessments of national characteristics in the comments of the recipients of journalistic publications are negative, due to the criticality and self-criticism of commentators.